Kathleen Collins The Black Essai Film - Ramanathan, Geetha (Edinburgh University Press, 2019)
A philosopher-filmmaker, Kathleen Collins decisively redefined the parameters of African American film with Losing Ground (1982). This book uses detailed analyses of Collins's films to contextualise her work in the African American, feminist and world film traditions, and it highlights her contribution to each of these canons.